Pengalruh laltihaln footwork terhaldalp kelincalhaln paldal ekstralkulikuler SMK Negeri 2 Terbalnggi Besalr - Atthollah, Ilham; Nugroho, Reza Adhi; Arifai, Arifai; Mahfud, Imam (Universitas Hamzanwadi, 2024)
This study aims to examine the effect of footwork training on student agility. This research method is experimental. The population in this study was 30 students. The technique of determining the sample using purposive sampling as many as 20 students. The data analysis technique of this research is paired sample test. The instrument used is shadow training. Based on these results, a correlation value of 0.896 was obtained, which means that there is a very strong relationship between pretest and posttest. From the pretest normality test data obtained with a value of 0.080 > 0.05 and posttest data with a value of 0.306 > 0.05, the data is normally distributed. Homogeneous test for pretest and posttest data is 0.058 which means > 0.05 the data is homogeneous. Data from the hypothesis test used to compare pretest and posttest results with a t value of 5.842 in the t table of 2.179 with a significant p value of 0.000. Therefore, t count 5.842 > t table 2.179 and a significant value of 0.000 < 0.05. From the data analysis, description, testing of research results, and discussion that has been done, it can be concluded that footwork training has an effect on increasing agility.